The Value of Routine Clinical and Radiologic Studies in Predicting Neoplastic Invasion of Cricoarytenoid Units - Çağlı, S.; Öztürk, M.; Yüce, İ.; Deniz, K.; Güney, E. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Evaluation of the laryngeal cartilages is essential for the treatment strategy of patients with laryngeal carcinoma. Our aim was to assess the accuracy of preoperative clinical examinations and CT for preoperative evaluation. MATERIALS AND METHODS: A prospective comparative study was performed at a university department on 30 patients with advanced laryngeal carcinomas. All patients were men and underwent total laryngectomy. The preoperative mobility of vocal folds was evaluated and classified as mobile, impaired, or fixed. CT was performed by using multidetector row CT. Cricoarytenoid units (CAUs) from the laryngectomy specimens were cut into sections. Histologic findings were compared with the clinical and radiologic findings. RESULTS: The accuracy of combined clinical and CT staging in CAUs with normal mobility, impaired mobility, and absent mobility and negative CT findings was 96.5%, 50%, and 80%, respectively. These scores were 40%, 54.5%, and 83.3% for CAUs with normal mobility, impaired mobility, and absent mobility and positive CT findings, respectively. CONCLUSIONS: Arytenoid mobility and >1 cartilage abnormality on CT were found to be reliable indicators of neoplastic cartilage invasion in patients with laryngeal carcinoma.